2020
DOI: 10.1080/13602365.2020.1733802
|View full text |Cite
|
Sign up to set email alerts
|

Providing care quality by design: a new measure to assess hospital ward layouts

Abstract: Which hospital ward layout works best? In the past, one response to this question has been to design layouts that minimise walking distances of healthcare workers, and increase the time spent with their patients. However, new research suggests that good face-to-face communication between doctors and nurses crucially impacts the health and safety of patients. Taking this into account, this research proposes a new single measure called Spaces for Communication Index (SCI). It assesses communication opportunities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…There were, however, important exceptions to these trends. In addition to the Blennerhassett et al (2018) pre and post ward redesign study, there were other targeted studies with quantitative observation data that similarly did not produce specific conclusions about the environment from their observation methods (Anåker et al, 2018; Broom et al, 2019; Edgerton et al, 2010; Lu & Zimring, 2012; Miller & Keith, 1973; Newall et al, 1997; Pachilova & Sailer, 2020; Scrivener et al, 2019; Shannon et al, 2019; Shepley, 2002; Stahler et al, 1984), and there were some notable examples of exploratory studies with qualitative observation data which did produce specific conclusions (Eriksson et al, 2010; Hamilton, 2019; Karlsson et al, 2019; Kelley et al, 2011; O’Hara et al, 2018). The conclusions drawn from these exploratory studies tended to be layered, with multiple implications for hospital design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were, however, important exceptions to these trends. In addition to the Blennerhassett et al (2018) pre and post ward redesign study, there were other targeted studies with quantitative observation data that similarly did not produce specific conclusions about the environment from their observation methods (Anåker et al, 2018; Broom et al, 2019; Edgerton et al, 2010; Lu & Zimring, 2012; Miller & Keith, 1973; Newall et al, 1997; Pachilova & Sailer, 2020; Scrivener et al, 2019; Shannon et al, 2019; Shepley, 2002; Stahler et al, 1984), and there were some notable examples of exploratory studies with qualitative observation data which did produce specific conclusions (Eriksson et al, 2010; Hamilton, 2019; Karlsson et al, 2019; Kelley et al, 2011; O’Hara et al, 2018). The conclusions drawn from these exploratory studies tended to be layered, with multiple implications for hospital design.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 37% of the included publications were classified as drawing specific conclusions from their observation data (n ¼ 25), 43% were classified as drawing nonspecific findings (n ¼ 29), and 19% could not be determined (n ¼ 13). Of the 29 studies with nonspecific findings, 59% were unspecific about both the environment and behavior in their results (n ¼ 17), while 41% were specific regarding particular aspects of behavior but provided limited information in regard to the environment (n ¼ 12), as in the Blennerhassett et al (2018) observation data that similarly did not produce specific conclusions about the environment from their observation methods (Ana ˚ker et al, 2018;Broom et al, 2019;Edgerton et al, 2010;Lu & Zimring, 2012;Miller & Keith, 1973;Newall et al, 1997;Pachilova & Sailer, 2020;Scrivener et al, 2019;Shannon et al, 2019;Shepley, 2002;Stahler et al, 1984), and there were some notable examples of exploratory studies with qualitative observation data which did produce specific conclusions (Eriksson et al, 2010;Hamilton, 2019;Karlsson et al, 2019;Kelley et al, 2011;O'Hara et al, 2018). The conclusions drawn from these exploratory studies tended to be layered, with multiple implications for hospital design.…”
Section: Aims Addressed and Conclusion Drawnmentioning
confidence: 99%
“…Additionally, it is suggested that spatial configuration can also influence the health performance of the building (Pachilova and Sailer, 2020). A recent study, for example, reported that higher visibility and accessibility led to a higher frequency of healthcare worker's hand-hygiene behaviours in hospitals (Cai et al, 2021).…”
Section: Architecture Health Indicesmentioning
confidence: 99%
“…The evidence-based design literature established connections between the physical environment and the experience of healthcare providers ( Ulrich et al., 2014 ). The available research on this connection focuses on the dynamics of movement patterns at the hospital level in general ( Choi, 2011 ; Yi and Seo, 2012 ), as well as within specialized units such as critical care units ( Cai and Zimring, 2012 ; Ossmann et al., 2019 ; Zadeh et al., 2012 ), medical-nursing units ( Pachilova and Sailer, 2020 ; Xuan et al., 2020 ), operating rooms ( Bayramzadeh et al., 2018 ), and the emergency department ( Rismanchian and Lee, 2017 ). At the unit level, research indicates that excessive and unnecessary movement caused by lengthy travel routes can result in fatigue, cause delayed task completion, or impair overall performance ( Zadeh et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in study on certain building styles that were suggested for staffing efficiency, decreased traveling distances for staff, and increased opportunities for patient observation, among other benefits ( Trites et al., 1970 ; Verderber and Fine, 2000 ). Radial corridor hospitals were popular in the 1960s ( Jaco, 1972 ; Pachilova and Sailer, 2020 ). Verderber and Fine (2000) also identified a variety of issues that have marked the transition of health care in their broad examination of the development of efficient health care architecture.…”
Section: Introductionmentioning
confidence: 99%